IMPACT OF COVID-19 ON MUTUAL FUND INVESTMENTS IN INDIA - Sindhu K. P. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The COVID-19 pandemic caused a significant disruption in global financial systems, including India's capital markets. The mutual fund industry, which had experienced consistent growth and increasing investor participation, faced unprecedented challenges due to market volatility, declining economic activity, and shifting investor behavior. This study aims to analytically assess the impact of COVID-19 on mutual fund investments in India by analyzing changes in investor behavior, fund performance, and risk perception during the pandemic. Using a sample size of 150 respondents collected through structured questionnaires and complemented by secondary data from the Association of Mutual Funds in India (AMFI), the study employs statistical tools such as descriptive statistics, paired t-tests, and regression analysis. The findings reveal a considerable decline in Systematic Investment Plan (SIP) volumes, increased redemptions, and a shift toward low-risk debt instruments. The paper concludes with implications for policymakers, fund managers, and investors.